2020
DOI: 10.1155/2020/5750370
|View full text |Cite
|
Sign up to set email alerts
|

Pricing Decisions in a Competitive Closed-Loop Supply Chain with Duopolistic Recyclers

Abstract: In this study, we consider a three-echelon closed-loop supply chain consisting of a manufacturer, a collector, and two duopolistic recyclers. In the supply chain, the collector collects end-of-life products from consumers in the market. Then, both recyclers purchase the recyclable waste from the collector, and each recycler turns them into new materials. The manufacturer has no recycling facilities; therefore, the manufacturer only purchases the recycled and new materials for its production from the two recycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Lee conducted an analysis of a third-order closed-loop supply chain comprising a manufacturer, a collector, and two duopoly recyclers. The findings of the study revealed that heightened price competition among recyclers had an adverse impact on the overall profitability of the supply chain [30]. Seyedhosseini et al conducted an analysis to examine the impact of different vertical game structures and the competitive game behaviours of two duopoly retailers on the overall profitability of the supply chain, the profitability of individual participants, and the optimal strategy.…”
Section: Competitive Supply Chainmentioning
confidence: 99%
“…Lee conducted an analysis of a third-order closed-loop supply chain comprising a manufacturer, a collector, and two duopoly recyclers. The findings of the study revealed that heightened price competition among recyclers had an adverse impact on the overall profitability of the supply chain [30]. Seyedhosseini et al conducted an analysis to examine the impact of different vertical game structures and the competitive game behaviours of two duopoly retailers on the overall profitability of the supply chain, the profitability of individual participants, and the optimal strategy.…”
Section: Competitive Supply Chainmentioning
confidence: 99%
“…In this direction, one can categorize the number of publishing articles into two groups. In the first groups, researchers mainly focused on the effect the information asymmetry in SC competition [31], Ai et al [32], Bian et al [33], Lee [34], and others. e authors explored optimal decisions mostly in a single game structure under price-dependent demand and explored the effect of information asymmetry in decentralized and centralized settings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We consider three types of pricing games: (i) a parallel pricing game, (ii) a sequential pricing game, and (iii) a unified pricing game. Duopoly markets consisting of two competitors can be found in various applications including supply chains [8,16], peak-load pricing [5], and two-tier service systems. An example of two-tier service is public healthcare service, which comprises free and paid service providers [17].…”
Section: Introductionmentioning
confidence: 99%